Echinoid skeletal carbonate as archive of past seawater magnesium isotope signatures – Potential and limitations. (15th August 2018) - Riechelmann, Sylvia; Mavromatis, Vasileios; Buhl, Dieter; Dietzel, Martin; Hoffmann, René; Jöns, Niels; Kell-Duivestein, Isaac; Immenhauser, Adrian
Abstract: The low-Mg (spine) to high-Mg (test) calcite skeletal hardparts of echinoids are exploited in carbonate archive research. These studies, however, are not coming without problems. Those rise from the solid phase metastability, the presence of amorphous precursors during biomineralization processes, the spatially variable skeletal Mg concentrations, and the porous microstructure at secretion of these biominerals. The present paper systematically evaluates the resilience of echinoid skeletal hardparts, here specifically sea urchin spines, to diagenetic alteration with a focus on magnesium isotope distribution (δ 26 Mg). We apply a dual approach by (i) performing alteration experiments using meteoric, marine, and burial model fluids and by (ii) comparing the experimental data with diagenetically overprinted fossil sea urchin hardparts. The degree of alteration of individual spines and an echinoid test was assessed by a combination of optical (fluorescence, cathodoluminescence (CL), scanning electron microscopy (SEM)) and geochemical tools (elemental distribution and δ 26 Mg). Magnesium isotope signatures of sea urchin spines are affected by experimental temperature, fluid composition, and duration of alteration experiment. Most strikingly, the recrystallization of spines from low-Mg (<5 mol% Mg fraction) to high-Mg or highest-Mg calcite (>5 up to 44 mol%) is observed throughout the experiments using burial and marine fluids at 175 °C. Simultaneously, δ 26 Mg values of progressively recrystallized Mg calcite are increasingly enriched in 26 Mg. Fossil spine material displays the highest Mg/Ca ratios and highest δ 26 Mg values, whereas a fossil (diagenetically overprinted) sea urchin test, formerly high-Mg and subsequently recrystallized to low-Mg calcite, displays the lowest δ 26 Mg values. These diagenetic features are in agreement with the data obtained from experimentally altered spines. The transformation of low- to high-Mg calcite of altered sea urchin hardparts is essentially controlled by the Mg content of the diagenetic fluid and directly affects the Mg isotope signature of the echinoderm skeleton. The experimental alteration data presented here mimic the patterns of Mg/Ca ratios and Mg isotope signatures of fossil echinoid skeletal hardparts as induced by diagenesis. Both, Mg/Ca ratios and isotope signatures of echinoderm hardparts are spatially and ontogenetically complex to start with and undergo significant and variable (fluid and carbonate composition-dependent) alteration processes in the presence of diagenetic fluids. These alteration processes include dissolution and re-precipitation reactions, but also diffusion between bulk and pore solution within the pore system of the sea urchin spine. The research shown here is significant as it documents the potential of a combined study using naturally and experimentally altered carbonate hardparts in an exemplary manner. Clearly, a critical approach to echinoid proxy archive for the reconstruction of past seawater Mg isotope composition is advised. In contrast, Mg isotope data and their changes in time and space have a significant potential to document processes and products resulting from diagenesis.